Design and Construction of a Single-Phase Synchronous Reluctance Motor Drive - Benjamin Akinloye (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2026)
Despite the advantages of synchronous reluctance motors (SynRMs) in terms of efficiency and cost, precise speed and torque control remains challenging under varying load conditions, particularly in single-phase configurations, which exhibit inherent torque pulsations and asymmetrical dynamics. This study aims to design, simulate, and implement a hybrid proportional-integral (PI)–Fuzzy Logic controller for single-phase SynRM drives to improve dynamic response and robustness over conventional methods. The research addresses the critical problem of maintaining fast transient response and minimal steady-state error under variable loads in single-phase SynRM systems. The control schemes were modeled in MATLAB/Simulink and implemented on an ATmega328P microcontroller interfaced with an infrared speed encoder. The ATmega328P was selected for its widespread availability, ease of integration, and sufficient processing power for low-power SynRM applications. Controllers were tested under variable load conditions simulating industrial and domestic use cases to assess performance under realistic dynamics. Among the three tested controllers—PI, Fuzzy Logic, and Hybrid PI–Fuzzy—the hybrid controller exhibited superior performance. The hybrid controller reduced overshoot by 40% and settling time by 35% compared to the standalone PI controller under identical test conditions. The field-oriented control algorithm was discretized for microcontroller implementation using fixed-point arithmetic to ensure compatibility with low-cost hardware. Experimental results confirmed accurate and stable speed tracking under dynamic conditions. This work contributes a low-cost, high-performance hybrid PI–Fuzzy control solution for SynRM drives, demonstrating the feasibility of implementing advanced control strategies on affordable embedded platforms.